ANALYSIS OF MOTIVATION IN STUDENTS OF THE ARCHITECTURE PROGRAM AT THE FRANCISCO DE PAULA SANTANDER UNIVERSITY. - Yannette Díaz Umaña; Giovanni Giraldo Guerra (DIALÉCTICA, 2025)
The purpose of this article is to present the results of the analysis of motivation in university students who begin their professionalization cycle of the architecture program at the Francisco de Paula Santander University. Motivation plays a fundamental role in the teaching-learning process of higher education students, since it influences interest, commitment, effort towards academic activities, permanence and promotion. Taking this importance into account, the conceptualization of intrinsic and extrinsic motivation is developed more as an emotional phenomenon than a cognitive one. The quantitative approach with a descriptive scope through the collection and analysis of data, allowed a statistical vision that facilitated the description of the motivational dimensions and identified the levels of academic satisfaction in 30 students who form the entire group of young people who begin said academic cycle. The instrument applied was the MAPE 3-M, digitized by Google forms software with Likert-type responses and applied on the university campus. This instrument of Spanish origin was adapted for this research, taking into account maintaining the dimensions (extrinsic motivation, intrinsic motivation and anxiety grouped in the seven factors) but reducing the number of questions to 42 to enable it to be successfully completed. The results are associated with greater involvement and active participation in classes, better academic performance, greater persistence and resilience, and development of self-regulation skills.